Carbohydrate mouth rinse improves performance of mentally fatigued cyclists despite null effects on psychological responses - Brietzke, C.; Vinícius, Í.; Ribeiro, W. A.; Franco-Alvarenga, P. E.; Canestri, R.; Vasconcelos, G. C.; Hettinga, F. J.; Santos, T. M.; Pires, F. O. (Physiology & Behavior, 2024)
Mental fatigue reduces exercise performance through an impaired psychological response such as increased perceived exertion. Carbohydrate (CHO) mouth rinses improve exercise performance and perceived exertion likely due to an improved activation in cerebral reward areas, then we investigated if the CHO mouth rinse-improved exercise performance in mentally fatigued individuals was associated with ameliorated reward-related psychological responses. We hypothesised that CHO mouth rinse would be beneficial for mentally fatigued cyclists mainly in high-metabolic disturbance intensities. After familiarization and baseline sessions, well trained cyclists (n = 20) performed a maximal incremental test (MIT) after mental fatigue induction. They completed the MIT either without mouth rinse (MF) or rinsing their mouth with CHO (MF+CHO) or placebo (FM+PLA) solutions at every 25 % of the MIT. Psychological responses such as ratings of perceived exertion (RPE), affective valence, emotional arousal, and motivation were assessed throughout the MIT, while performance was assessed as peak power output and time of exercise. Mental fatigue reduced MIT performance (P < 0.05), but CHO mouth rinse was effective to counteract this deleterious mental fatigue effect (P < 0.05). However, we found null effects of CHO mouth rinses in psychological responses above the VT2 (P > 0.05) such as RPE, affective valence, emotional arousal, and motivation. Correlational analysis showed a significant, but moderate negative correlation between motivation and time of exercise above the VT2 when participants used CHO mouth rinse. In conclusion, the ergogenic CHO mouth rinse effects on MIT performance of mentally fatigued cyclists were irrespective of ameliorated psychological responses to exercise.